Re-emergence of fatal human influenza A subtype H5N1 disease - Peiris, JSM (Lancet, 2004)
Human disease associated with influenza A subtype H5N1 reemerged in January, 2003, for the first time since an outbreak in Hong Kong in 1997. Patients with H5N1 disease had unusually high serum concentrations of chemokines (eg, interferon induced protein-10 [IP-10] and monokine induced by interferon γ [MIG]). Taken together with a previous report that H5N1 influenza viruses induce large amounts of proinflam-matory cytokines from macrophage cultures in vitro, our findings suggest that cytokine dysfunction contributes to the pathogenesis of H5N1 disease. Development of vaccines against influenza A (H5N1) virus should be made a priority.